Desvelando o gênero discursivo da atividade profissional docente: análises de autoconfrontações de estagiárias de inglês do alto Sertão Paraibano - Mussi, Marcus Vinícius Freitas (2019)
This is a research of an interpretative nature and affiliated to Applied Linguistics. The objective here was to analyze enunciative mechanisms, (re)positioning and conflicts in speeches of English-speaking trainees from the high backlands in Paraíba in order to reveal constitutive aspects of this genre. To do so, we have organized our theoretical framework basically into two large blocks. The first one refers to the English language traineeship in public schools in Brazil, which we seek to base with government sources, such as laws and research from INEP1 , among others, as well as authors such as Paiva (2003) and Teixeira (1996). In this block, there are still the postulates of Applied Linguistics, more precisely about the "voices of the south" and inter / transdisciplinarity. The second theoretical block is made up of discussions about the work of the teacher, focusing on linguistic issues, which in turn are addressed in Sociodiscursive Interactionism (SDI), according to Bronckart (2003 [1999], 2006 and 2008), Bronckart and Machado (2007), and Machado and Bronckart (2009). This theoretical contribution offers us tools for linguistic-discursive analysis (BRONCKART, 2003 [1999]). And among its different possible mechanisms, we focus on the enunciative level. In addition to this second block, there are the postulates of the Labor Sciences, linked to Amigues (2004), and Clot and Faita (2016 [2000]), from where we have adopted simple and cross-checking self confrontation procedures to investigate the gender of English trainees of the high backlands of Paraíba. Two trainees from the undergraduate course in Letters-English in Cajazeiras-PB were the participants, who worked in the town of origin: Poço José de Moura-PB and São José de Piranhas-PB. The partial analysis revealed the recurrent themes in the participant trainees‟ discourses about the classroom, which, in turn, were compared with some results obtained by Pereira (2016) from IFPB teachers' discourses on the same theme with self confrontation procedures. The results showed, among other aspects, that the traineers put themselves in the center of the autoconfrontation evaluation process, evaluating their own action; that the traineer´s power of acting was maximized from the beginning to the end of the internship; that there is progress from academic acting to professional acting in the traineer´s discourses along the internship; that there are two senses on the renew of the genre: flexibilization on the application of rules and the customization enrichment; that there is some variation on power of acting between the traineer´s beginning (academic acting) and professional practice (professional acting) that narrow cultural aspects though the language can offer better comprehension of its own one, but it´s needed to be aware about acculturation in the sense of a culture overlaps another. With this, we support the thesis that it is possible to unveil constitutive aspects of professional teaching activity based from an analysis English teacher trainees´ speeches of the high backlands of Paraíba